Development of genetic SSR markers in Blumeria graminis f. sp. hordei and application to isolates from Australia - Tucker, Madeline; Moffat, Caroline; Ellwood, Simon; Tan, Kar-Chun; Jayasena, K.; Oliver, Richard (Wiley-Blackwell, 2015)
The barley powdery mildew pathogen, Blumeria graminis f. sp. hordei (Bgh), exists in numerous haplotypes and displays significant differences in fungicide sensitivity. It causes considerable yield losses throughout the world. Microsatellite SSRs are useful tools to study the population level and biogeographic aspects of intraspecific diversity, but so far none have been defined for Bgh. Here, eight polymorphic microsatellite loci were identified and characterized. Primer pairs amplifying the loci were then applied to 111 isolates of Bgh from Australia. The number of alleles per locus ranged from 4 to 13, and Nei's genetic diversity ranged from 0·25 to 0·76. The microsatellite primers detected several clones among the isolates and defined 97 unique haplotypes. There was little evidence for regional genotypic subdivision, suggesting that gene flow may not be restricted among geographic regions. All data was consistent with high levels of genetic diversity, potentially resulting from random mating and spread within each region.